Kepemimpinan Abdurrahman Ad-Dakhil Dalam Dinamika Politik Bani Umayyah di Andalusia - Muhammad Mastuhan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study explains the leadership of Abdurrahman Ad-Dakhil in the political dynamics of the Umayyad dynasty in Andalusia in the 8th century AD. The purpose of this study is to explain Abdurrahman's strategy to rebuild Umayyad power, organize the fragmented political structure, and create stability that is acceptable to various groups in society. This study uses historical methods, including source collection, criticism, analysis, and historical writing to observe the political conditions of Andalusia after the initial conquest. The results of this study are Abdurrahman's success in uniting Arab, Berber, and local communities, strengthening professional troops, and centralizing administration in Cordova. His leadership restored political order and formed a new political identity independent of the center. This foundation became the starting point for the development of the economy, culture, and science during the dynasty that followed him. This study shows that Abdurrahman Ad-Dakhil's leadership can be understood as a form of Islamic political leadership that is able to unite various elements of society, adapt to the conditions faced, and is relevant to studying the dynamics of the development of Islamic government during the classical period.